Sodium Bicarbonate for In-Hospital Cardiac Arrest - Asger Granfeldt; Bertram Lahn Kirkegaard; Mikael Fink Vallentin; Mathias J. Holmberg; Nikola Stankovic; Peter Carøe Lind; Anders Gade Kjærgaard; Nanna Houe; Matias Vested; Dan Lou Isbye; Camilla Meno Kristensen; Jesper Kjærgaard; et al. (JAMA, 2026)
Importance Patients with in-hospital cardiac arrest have poor outcomes. Sodium bicarbonate is commonly administered during cardiac arrest, but the effects on clinical outcomes are unknown. Objective To determine whether administration of sodium bicarbonate during in-hospital cardiac arrest increases the proportion of patients with return of spontaneous circulation. Design, Setting, and Participants Randomized, parallel-group, double-blind, placebo-controlled clinical trial conducted at 21 hospitals in Denmark. Participants were adults with in-hospital cardiac arrest, who received at least 1 dose of epinephrine. Patients were enrolled from February 6, 2023, to February 11, 2026, with the last 90-day follow-up conducted on May 4, 2026. Final statistical analysis was conducted on May 5, 2026. Intervention Sodium bicarbonate (up to 100 mmol) or placebo intravenously. Main Outcomes and Measures The primary outcome was sustained return of spontaneous circulation. Key secondary outcomes were survival at 30 days and survival at 30 days with a favorable neurologic outcome, defined by a score of 0 to 3 on the modified Rankin Scale (scores range from 0 to 6, with higher scores indicating greater disability). Results A total of 2913 patients with in-hospital cardiac arrest were screened; 913 patients were randomized, of which 779 were eligible for the primary analyses, with 372 randomized to receive sodium bicarbonate and 407 randomized to receive placebo. The median (IQR) age of patients was 73 (64-79) years and 502 were male (64%). Sustained return of spontaneous circulation occurred in 146 patients (39%) in the sodium bicarbonate group and 150 (37%) in the placebo group (risk ratio, 1.05 [95% CI, 0.88-1.24]; P = .62). At 30 days, 45 patients (12%) in the sodium bicarbonate group and 37 (9.1%) in the placebo group were alive (risk ratio, 1.25 [95% CI, 0.84-1.88]); a favorable neurologic outcome at 30 days occurred in 30 patients (8.1%) and 22 patients (5.4%), respectively (risk ratio, 1.39 [95% CI, 0.82-2.34]). Alkalosis and hypernatremia after cardiac arrest were more common in the sodium bicarbonate group. Conclusions and Relevance There was no significant difference in sustained return of spontaneous circulation between sodium bicarbonate and placebo in adults with in-hospital cardiac arrest. These findings do not support routine administration of sodium bicarbonate for patients with in-hospital cardiac arrest. Trial Registration ClinicalTrials.gov Identifier: NCT05564130 ; ClinicalTrialsRegister.eu Identifier: 2022-501304-10-00